2015
DOI: 10.1038/onc.2015.208
|View full text |Cite
|
Sign up to set email alerts
|

OTUB1 inhibits the ubiquitination and degradation of FOXM1 in breast cancer and epirubicin resistance

Abstract: The forkhead transcription factor FOXM1 has a key role in DNA damage response, and its deregulated overexpression is associated with genotoxic drug resistance in breast cancer. However, little is known about the posttranslational mechanisms by which FOXM1 expression is regulated by genotoxic agents and how they are deregulated in resistant cells. Initial co-immunoprecipitation studies verified previous proteomic analysis finding that the OTUB1 is a novel FOXM1-interacting protein. Western blot analysis showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(98 citation statements)
references
References 36 publications
5
90
1
Order By: Relevance
“…Moreover, elevated expression of OTUB1 predicts poor prognosis in ovarian cancer. Indeed, it has been reported that OTUB1 could enhance breast cancer chemoresistance [35]. Based on the relationship between OTUB1 and FOXM1, and FOXM1's enhancement of ovarian cancer chemoresistance, [36] the effect of OTUB1 and the OTUB1-FOXM1 axis on ovarian cancer chemoresistance is a curious question for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, elevated expression of OTUB1 predicts poor prognosis in ovarian cancer. Indeed, it has been reported that OTUB1 could enhance breast cancer chemoresistance [35]. Based on the relationship between OTUB1 and FOXM1, and FOXM1's enhancement of ovarian cancer chemoresistance, [36] the effect of OTUB1 and the OTUB1-FOXM1 axis on ovarian cancer chemoresistance is a curious question for future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further encouraged by new evidence indicating that FOXM1 (1) drives tumor development and progression 1519 by virtue of a complex mechanism that includes enhanced cell proliferation, migration and invasion 6 , regulation of the DNA damage response 20 and changes in the cancer epigenome 21 , (2) promotes cancer-cell resistance to ionizing radiation 22 and cytotoxic drugs 23 , (3) governs, in part, the survival and tissue-regenerating capacity of both normal hematopoietic stem cells 24 and malignant stem cell-like cells 25 , (4) links acquired resistance to cancer therapy with cancer stemness 26 and (5) owing to the development of specific small-molecule inhibitors 27 , may soon be targeted more effectively than possible in the past 28 , we here decided to evaluate whether FOXM1 might play an important but heretofore overlooked role in plasma cell myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…OTUB1 is abnormally up‐regulated in somatic malignancies and exerts oncogenic functions 26, 32, 33, 34. We have also previously demonstrated that OTUB1 prompted tumour growth and metastasis in ovarian cancer and gastric carcinoma 25, 29.…”
Section: Discussionmentioning
confidence: 80%